Gut microbiota and calcium balance - Wang, Jiali; Wu, Shuang; Zhang, Yinshan; Yang, Jiao; Hu, Zhongliang (Frontiers in Microbiology, 2022)
Microorganisms living on the surface and inside the human body play an important role in the physiological activities of the human body. The largest microecosystem in the human body is the gut microbiome. Calcium disorders are found in many diseases. For example, patients with chronic renal insufficiency present with secondary hyperparathyroidism, which is caused by a calcium imbalance in the body. In addition, calcium dysregulation may affect lipid metabolism in the liver through the calmodulator pathway, leading to cirrhosis, etc. Currently, a considerable number of probiotics have been proven to enhance the body's absorption of calcium. This paper reviews the effects of intestinal flora and related factors such as short-chain fatty acids, estrogen, immune factors and vitamin D on calcium balance.